Biological Synthesis and Characterization of Silver Nanoparticles Using Bacillus Subtilis - Ayad F. Alkaim (Journal of Global Pharma Technology, 2017)
Biological synthesis of silver nanoparticles using Bacillus subtilis was examined and reported. The quick reduction of silver (Ag+) ions was checked using UV-visible spectrophotometers and showed formation of silver nanoparticles within 1 hr. Transmission electron microscopy (TEM) investigation presented that the synthesized silver nanoparticle are 39.6 nm and has spherical shape. Additional the XRD analysis approves the Nano crystalline phase of silver with FCC crystal structure.Keywords: Nanoparticles; Silver; Bacillus subtilis.